KAJIAN LINGKUNGAN TEMPAT PEMILAHAN SAMPAH DI KOTA MAKASSAR - Asmi Citra Malina; Suhasman Suhasman; Asikin Muchtar; Sulfahri Sulfahri (Jurnal Inovasi dan Pelayanan Publik Makassar, 2017)
This study aims to evaluate the existing condition of waste sorting place in Makkassar City and the existing regulations in supporting the handling of waste in Makassar City in order to produce formulation of waste sorting system from household to TPS. Methods of data collection used in this study are: (1) study of literature and regulation, and waste management system in several cities and major countries to be adopted in Makassar; (2) field survey to find out the complaints in the community around the place of sorting of garbage; (3) Focus Group Discussion (FGD) from various stakeholders including the community around the place of waste segregation and related SKPD. Likert scale (as one of attitude scale) for the development of statistical analysis technique where ordinal data is converted to interval data, the result will be analyzed using Analytic Hierarchy Process (AHP) to formulate policy about septic and environmentally friendly waste separation place in Makassar City. The result of the research shows that: (1) Waste Bank and TPS3R in Makassar city can improve the economy of society and reduce unemployment, (2) Waste Bank in Makassar city acceptable to society and not cause negative impact, (3) TPS3TR in Makassar City according to people's perception around the location can make dirty air due to dust and environmental smoke, (4) TPS3TR in Makassar City according to the perception of the people around the location can disrupt the general traffic around the TPS3R location, (5) Garbage Bank and TPS3R in Makassar City can improve people's economy and reduce unemployment.